Paleoecology of Glacial and Non Glacial Carboniferous Faunas During the Late Paleozoic Ice Age in Patagonia - (:unkn) unknown (My University, 2015)
The Late Paleozoic Ice Age (LPIA) records the only icehouse to greenhouse transition in Earth’s history that involved complex marine and terrestrial life and serves as an analogue for Quaternary climate change. Identifying biotic responses to paleoenvironmental variations during the LPIA is important in order to understand how our modern fauna may respond to contemporary climate change. Low-paleolatitude (far-field) marine faunas far from ice centers have been recognized and used as a global proxy for biotic responses to the LPIA, but the biotic responses in high-paleolatitude (near-field) regions close to Gondwanan ice centers have received much less attention. We tested the hypothesis that paleocommunities within polar latitudes in glacially influenced marine environments differed ecologically from paleocommunities distal to glacial influence. This study focused on the paleoecology of the Tepuel-Genoa Basin located in central Patagonia, Argentina to determine how conditions during the LPIA influenced marine paleoecology in a near-field region. Quantitative stratigraphic and paleontological analyses were conducted on sections near the base of the Pampa de Tepuel Formation. Results from this study suggest that paleocommunities located near the base of the formation were affected by stressful physical processes from glacial influences and possible small debri flows. Paleoecommunities were dominated by sessile epifaunal suspension feeders, abundant crinoid populations, and a lack of durophagus predation. This data suggests that Paleozoic marine invertebrate communities in a near-field region during the LPIA can be used as a potential proxy for modern glacial-marine communities. It is interpreted that shifts in taxonomic composition occur throughout this basin depending on environmental influences. The paleoecological changes observed in the Pampa de Tepuel Formation could be indicative of the waxing and waning of glaciation or of glacial and non-glacial intervals during this ice age.
Keywords: Argentina; Carboniferous; Ice Age; Late Paleozoic; Paleoecology